Beyond fungicides: embracing bioformulation innovation in mitigating white root rot disease impact on rubber plantations - Shabbir, Imran; Wong, Mui-Yun; Sulaiman, Zulkefly; Shahbaz, Muhammad; Khan, Iqra; Rizwana, Humaira; Elshikh, Mohamed Soliman; Adil, Muhammad Faheem (Springer Science and Business Media LLC, 2024)
The white root rot (WRR) disease poses a formidable economic challenge to rubber plantations globally, with Malaysia particularly hard-hit. This disease is attributed to Rigidoporus microporus. This glasshouse experiment investigated the effects of a stored, peat moss-based formulation containing silicon (Si), Glomus mosseae, and Enterobacter sp. UPMSSB7 on combatting WRR and promoting the growth of rubber plants. Compared to the positive control, the experimental bioformulation significantly reduced disease incidence (P < 0.0001), with efficacy comparable to the propiconazole fungicide. Furthermore, the bioformulation and fungicide treatments demonstrated superior disease mitigation compared to the positive control 24 weeks after R. microporus-inoculation. The bioformulation treatment not only reduced disease incidence and mitigated foliar and root rot symptoms, but it also resulted in a lower disease progressive curve and reduced R. microporus colonisation. Additionally, bioformulation significantly increased (P < 0.001) plant growth parameters 24 weeks after R. microporus inoculation. These parameters included stem height, girth size, chlorophyll content, leaf area, root and shoot dry weight, root volume, total root length, and root surface area. These effects surpassed those observed in fungicide and control treatments. The Si content in shoot and root and leaf N, P, and K nutrient contents were also significantly (P < 0.001) increased in the R. microporus-inoculated plants with the tested bioformulation than the fungicide and control. In the case of R. microporus-inoculated plants of bioformulation treatment, there was a significant (P < 0.001) increase in the population density of Enterobacter sp. (1.5 × 108 cfu g− 1 soil), surpassing the levels observed in non-inoculated plants of bioformulation and inoculants with Si, with or without R. microporus-inoculation. Moreover, bioformulation treatments improved (P < 0.001) root colonisation as well as spore density of G. mosseae after R. microporus-inoculation than control and fungicide. This study suggests that a peat-based bioformulation containing G. mosseae, Enterobacter sp., and Si could be an effective strategy for both enhancing plant growth and mitigating WRR in rubber plants.